Hubungan Antara Pengetahuan Dengan Pelaksanaan Sistem Lima Mejadi Posyandu Balita Kelurahan Ngronggo Kecamatan Kota Kota Kediri - Dwi Rahayu; Moh Alimansur; Fajar Rinawati (coba, 2012)
Posyandu is a place to get basic services, especially in areas that are managed by the public health. Posyandu function is not optimal in fourth table or a healt promotion table has not been fully utilized by the cadres. Many of those who did not provide information at the time of weighing every month. The purpose of this study was to determine the relationship between knowledge and implementation the five tables systems in Posyandu balita the Ngronggo Village, Kediri. The population in this study is all cadres posyandu balita who was in the district Ngronggo Kediri which totaled 57 people. Number of samples taken as many as 52 people. The sampling technique used is proportioned random sampling. Analysis of the relationship between knowledge and implementation the five tables systems is Spearman rho correlation. From the processing of the analysis statistic obtained probability value is more than 0.05, which means there is no relationship between knowledge and implementation the five tables systems in Posyandu balita the Ngronggo Village, Kediri City. The results showed the cadres who have obtained the information and training has been attempted to try (trial) and try to adopt all the knowledge gained to apply when posyandu but because it is constrained by a variety of conditions such as facilities and infrastructure, the less number of cadres, many cadres who had elderly so that their knowledge can not be fully used when posyandu